C-Reactive Protein-to-Albumin Ratio as an Early Biomarker to Identify Sepsis in Neonates with Pneumonia. (14th July 2022) - Kang, Ping; Kang, Wen; Li, Yi; Li, Tiewei
Abstract : Objectives . Neonates with pneumonia often also have sepsis, and the identifying sepsis from pneumonia may be a challenge for clinicians. However, there are no available data regarding the clinical value C-reactive protein-to-albumin ratio (CAR) in identifying sepsis in neonates with pneumonia. The aim of this study was to evaluate the clinical value of CAR in identifying sepsis in neonates with pneumonia. Methods. 847 neonates with pneumonia were included in this study, of which 511 neonates were diagnosed with sepsis. Neonates were divided into the sepsis group and the nonsepsis group. All neonates underwent extensive and necessary clinical and laboratory tests. CAR was calculated as serum C-reactive protein (ng/ml)/albumin (mg/ml). All statistical analyses were performed using the statistical package SPSS 24.0, as appropriate. Results . Compared with the nonsepsis group, neonates with sepsis have a higher CAR (P < 0.001 ). Further analysis showed that the prevalence of neonates with sepsis increased significantly from 41.0% in the low CAR group (CAR ≤ 0.024 × 10 − 3 ) to 80.0% in the high CAR group (CAR > 0.024 × 10 − 3 ) (P < 0.001 ). Correlation analysis showed that there was a strong positive correlation between CAR and PCT (r = 0.452, P < 0.001 ), nSOFA (r = 0.267, P < 0.001 ), and the prolonged length of hospital stay (r = 0.311, P < 0.001 ). Multiple logistic regression showed that CAR was an independent risk factor for the presence of sepsis in neonates with pneumonia. Receiver operating characteristic curve analysis revealed that CAR had adequate discriminatory power in predicting sepsis in neonates with pneumonia (area under curve AUC = 0.76, 95% CI 0.73-0.79, P < 0.001 ). Conclusions . CAR can be used as a new marker to identify sepsis in neonates with pneumonia.